(untitled) (Journal of Accounting and Financial Studies ( JAFS ), 2018)
The Research topic seeks to analyze the "political risk and its component Terrorism Index," which consists of five indicators index, a number of terrorist operations, and the number of dead and wounded, and the size of the physical losses, based search sub-index analysis of material losses for the index terrorism and its impact on the indicators listed on the Iraq Stock Exchange Finance. As for the practical side, it has been use style gradient unrestricted and link the sample represented by ten banks listed on the Iraq Stock Exchange. was Statement the correlation and interaction of variables of the studySearch results produced that the volume of material losses is the most important indicator in the influential force and it explain a value (86%) of the variables in indicators of Iraq Stock Exchange It is belonging to it and this is a logical conclusion of the fact that material losses index is a direct impact on the economic situation, Especially in years of the study of the result of the fires and the sabotage of infrastructure and public facilities of the state As well as important business areas, The remainder, amounting to (14%) is attributed to the contribution of other variables